2002
DOI: 10.1021/bi025936u
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transforming Growth Factor-β Signaling by Low Molecular Weight Compounds Interfering with ATP- or Substrate-Binding Sites of the TGFβ Type I Receptor Kinase

Abstract: Transforming growth factor-beta (TGFbeta) is a potent regulator of cell proliferation, differentiation, apoptosis, and migration. TGF-beta type I receptor (TbetaR-I), which has intrinsic serine/threonine kinase activity, is a key component in activation of intracellular TGFbeta signaling. We studied two different classes of TbetaR-I inhibitors, i.e., compounds interfering with the ATP-binding site of the kinase and substrate-mimicking peptides. We found that pyridinylimidazole compounds inhibited TbetaR-I kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…44,46,49,51,62 First, the effects of p38MAPK rely largely on biological context, particularly the intensity and duration of kinase activity. 52 Second, although SB203580 is relatively specific for blocking p38MAPK, it has been reported to target other signaling pathways, such as cyclin G-associated kinase and SMAD 63,64 ; thus, we cannot exclude an off-target effect of SB203580 on VSMC differentiation, particularly at higher concentrations (eg, 10 μmol/L). In this context, we have found that both SB203580 and BIRB (another p38MAPK inhibitor) augment levels of VSMC marker expression at low concentrations, whereas inhibition is seen at higher concentrations ( Figure VII in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 97%
“…44,46,49,51,62 First, the effects of p38MAPK rely largely on biological context, particularly the intensity and duration of kinase activity. 52 Second, although SB203580 is relatively specific for blocking p38MAPK, it has been reported to target other signaling pathways, such as cyclin G-associated kinase and SMAD 63,64 ; thus, we cannot exclude an off-target effect of SB203580 on VSMC differentiation, particularly at higher concentrations (eg, 10 μmol/L). In this context, we have found that both SB203580 and BIRB (another p38MAPK inhibitor) augment levels of VSMC marker expression at low concentrations, whereas inhibition is seen at higher concentrations ( Figure VII in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 97%
“…TGF-b1-induced IL-6 expression was significantly suppressed by NF-kB inhibition, and pretreatment of p38 inhibitors SB202190 and SB203580 blocked NF-kB activation. However, it should be noted that SB203580 and SB202190 are also able to suppress TGF-b-specific response by interfering with the ATP-binding site of TbR-I (Yakymovych et al, 2002). Additionally, we identified that inhibitory effect of SB202190 on IL-6 expression is less significant compared to IkBDN or MG132, leading to the conjecture that NF-kB could also be activated by a mechanism(s) distinct from the p38 cascade in TGF-b1-treated prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides used in this study were synthesized using the Fmoc (N-(9-fluorenyl)methoxycarbonyl) chemistry as described (20). Three lysine residues were added to the N terminus of each peptide to allow peptide binding to the P81 phosphocellulose paper or to the plastic.…”
Section: Methodsmentioning
confidence: 99%
“…Gels were dried and exposed by phosphorimaging. Phosphorylation of GST-Smad2 proteins in vitro was performed as described earlier (20). After SDS-PAGE, the proteins were transferred onto the nitrocellulose membrane, and phosphorylation of the C terminus was analyzed by two-dimensional phosphopeptide mapping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation